Vertical Electrical Sounding Method to Detect Groundwater and Design of A Tubular Well for the Pampas District – Peru - Chavez Pacheco, Maria del Pilar (2023)
In recent years, the occurrence of unexpected meteorological events during the dry season and population growth have generated shortages in the supply of drinking water in the city of Pampas. This situation led us to look for new search strategies for natural water sources, even underground. Faced with this problem, the possibility of detecting and parameterizing these sources was raised, while the design of a tubular well was raised that allows the economic extraction of water from the aquifer studied through the use of geophysical techniques, generating profile images of geological maps. of the strata and the location of the possible water table of the study area. The preferred locations for locating groundwater collections are alluvial fans and fractured valley bottoms. Using the Schlumberger array, eleven (11) VESs have been made, up to a depth of 150 m. For the field tests, a resistivity meter that we have manufactured by hand was used, this will emit current to the subsoil obtaining layers and horizons through their resistivities, these values vary in the range of 6.32-125.23 Ω.m. The PQWTS-150- Water Detector equipment was also used to measure the depth of the semi-confined aquifer and to know its groundwater flow, the value is 33.33 l/s, this value refers to the three celestial layers that can be seen in the image. description of the profile of the geological map, in this profile clayey, silty, sandy, gravel soils and a combination of them were found. This point 11 was taken in the nursery of the Daniel Hernández district, this area is flat, quite humid and its depth is 51m -115m. In addition, this aquifer has good hydrogeological possibilities making surface recharge possible. The water table was also determined, it is found at a depth of 4-8 m. With the data obtained lines above it was useful for the calculation and design of the tubular well. In conclusion, the designed well has a depth of 115 m and a thickness of 64 m, with a drilling diameter of 18 inches and equipped with a submersible pump with a 25 HP motor, achieving a flow rate of 1000 l/min, which complies with the water requirement of the population. In order to verify the quality of the water from this well, a physical-chemical and bacteriological analysis was carried out.